Perhitungan Iuran Dana Pengembangan Pendidikan dengan Menggunakan Metode ABC Pada Sekolah Raudatul Ilmi di Kota X - Devi, Fitriyah Kusuma (Equity: Jurnal Akuntansi, 2024)
This study aims to calculate tuition fees appropriately and fairly at Raudatul Ilmi School in X City using the Activity Based Costing (ABC) Method and to find out the differences between the Traditional Method and the ABC Method. This research uses qualitative methods that collect data using interviews and documentation. The analysis technique used by this research uses descriptive analysis. The results obtained are the calculation of the tuition fee rate using the Traditional method shows the Play Group (KB) level rate of Rp 130,220, the Kindergarten (TK) level of Rp 168,315, the ABC calculation shows the KB level rate of Rp 160,055 and the Kindergarten level of Rp 200,561. These results cause undercosting at Raudatul Ilmi School.